Hydroxypropyl methacrylate thin film coating on polyvinylidene fluoride hollow fiber membranes via initiated chemical vapor deposition. (5th January 2020) - Subramaniam, M.N.; Goh, P.S.; Sevgili, E.; Karaman, M.; Lau, W.J.; Ismail, A.F.
Graphical abstract: Highlights: Successful coating of HPMA thin film on PVDF membranes in low temperature. Characterizations indicated successful growth of HPMA thin film on PVDF membrane. Coating greatly enhanced membrane hydrophilicity and reduce surface roughness. Enhanced membrane permeation and rejection performance. Easy coating in highly controlled environment. Abstract: Thin films of hydroxypropyl methacrylate (HPMA) were grown on polyvinylidene fluoride (PVDF) hollow fiber membranes via initiated chemical vapor deposition (iCVD), utilising di- tert -butyl peroxide as radical initiator. This method was able to completely coat PVDF membranes, producing uniform deposition of hydrophilic HPMA of 50 nm and 100 nm thickness on the membrane surface. The deposition of HPMA layer has been evidenced from the microscopy images and Fourier transform infra-red spectra. The HPMA coated membranes exhibited significantly improved surface hydrophilicity as reflective from the reduction in water contact angle from 78.1° to 23.6° meanwhile the membrane surface roughness was reduced with the thin film coating. The separation performance of HPMA-PVDF membranes was evaluated in the treatment of in-house prepared synthetic aerobically-treated palm oil mill effluent (AT-POME), which consists of lignin and tannic acid (TA). 100HPMA-PVDF membranes exhibited improved membrane flux and rejection of 50.8L/m 2 h and 83.1%, respectively. Additionally, 100HPMA-PVDF membrane maintained stable high permeation and rejection properties after four filtration cycles, due to its greatly improved surface hydrophilicity and reduced surface roughness. The studies open possibilities for highly controlled surface modification of membranes using low temperature iCVD methods to tailor the membrane selective layer.